2011
DOI: 10.3892/or.2011.1228
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the cervical stump: Fifty years of experience

Abstract: Abstract.A series of patients with carcinoma of the cervical stump in relation to age, clinical stage, histopathology, changes in relative incidence, treatment outcome and longterm survival, were studied and the findings were compared with matched controls that have an intact uterus and cancer of the cervix. of 8,028 women treated for invasive cervical carcinoma between 1959-2004, 161 were diagnosed with stump cancer, accounting for 2.0% of all cervical cancers. the mean time interval between subtotal hysterec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Therapeutic strategies and overall prognosis do not differ to those with an intact uterus, although it is suggested that early-stage carcinoma of the cervical stump is found rarer compared to cervix carcinoma of an intact uterus [ 19 ]. Thus, it can be presumed that cervical stump cancers have a poorer prognosis due to higher stage at diagnosis compared to cervical cancer cases in patients with intact uterus [ 20 ]. Hellström et al [ 21 ] reported no poorer prognosis after radiologically treated squamous cervix carcinoma of the uterine stump compared to patients with intact uterus with an increased complication rate in stump cancer cases, presumably due to anatomic modifications in the pelvis following a LASH [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic strategies and overall prognosis do not differ to those with an intact uterus, although it is suggested that early-stage carcinoma of the cervical stump is found rarer compared to cervix carcinoma of an intact uterus [ 19 ]. Thus, it can be presumed that cervical stump cancers have a poorer prognosis due to higher stage at diagnosis compared to cervical cancer cases in patients with intact uterus [ 20 ]. Hellström et al [ 21 ] reported no poorer prognosis after radiologically treated squamous cervix carcinoma of the uterine stump compared to patients with intact uterus with an increased complication rate in stump cancer cases, presumably due to anatomic modifications in the pelvis following a LASH [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our second patient makes a convincing case for "postmenopausal" vaginal bleeding due to PV. Here, a resection of the cervical stump was recommended because of a heightened concern for stump cervical squamous or endometrial adenocarcinoma (22)(23)(24) and was avoided because of reconsideration of the findings in light of the history of PV.…”
Section: Discussionmentioning
confidence: 99%
“…Carcinomas of the cervical stump after subtotal hysterectomy are not uncommon with an incidence of 0.1-3 %. Among these carcinomas, approximately 88 % were squamous cell carcinoma and the remaining were adenocarcinoma [ 31 , 32 ]. However, we could not find any reports on adenocarcinoma or serous EIC arising in endometriosis (adenomyotic cyst) of the cervical stump in English literature to date.…”
Section: Discussionmentioning
confidence: 99%